Applications of Triple Integrals (International Journal of Scientific Research in Science and Technology, 2025)
This paper presents a comprehensive study of triple integrals, extending the conventional understanding of volumetric integration to encompass a broader class of functions and domains. We introduce a novel framework for defining and evaluating these integrals, particularly focusing on cases where the integrand or the region of integration exhibits discontinuities, singularities. Utilizing concepts from measure theory and functional analysis, we develop techniques for establishing the existence and uniqueness of total triple integrals under relaxed regularity conditions. A significant contribution is the establishment of a generalized total triple integrals. We further explore applications of these integrals in physics, specifically in modelling heterogeneous materials and non-equilibrium systems, where conventional integration methods prove inadequate. Triple integrals play a crucial role in various digital applications, particularly in fields like computer graphics, image processing, machine learning, and signal processing. These integrals enable the computation of volumetric properties, aiding in tasks such as 3D rendering, object recognition, and spatial data analysis. In computer graphics, triple integrals help simulate realistic lighting, shading, and textures. In image processing, they assist in reconstructing 3D models from medical scans and volumetric data. Machine learning utilizes triple integrals in probability density estimation and feature extraction from multidimensional datasets. Other applications include 3D scanning, AR/VR development, and robotics, where they contribute to path planning and spatial mapping. Overall, triple integrals are indispensable in advancing digital technologies that rely on 3D data representation and analysis.